Age-dependent hormesis-like effects of the synthetic cannabinoid CP55940 in C57BL/6 mice - Erik L. Hodges (Nature Portfolio, 2020)
Abstract Use of cannabis and cannabinoid-containing substances is increasing among geriatric patients, despite relatively sparse preclinical evidence in aged models. To better understand the effects of exogenous cannabinoids on aging male and female rodents, we compared the age- and dose-dependent physiological and behavioral effects of the synthetic cannabinoid CP55940 in young–adult and aged C57BL/6 mice. Locomotion, body temperature, thermal nociception, and fecal output were measured following CP55940 administration. Our findings indicate that CP55940 is more potent and efficacious in older mice, evidenced by exaggerated antinociception and locomotor inhibition when compared to younger adult mice. In addition, we report that low doses of CP55940 paradoxically stimulate locomotion in young–adult (4 m) mice; however, this hormesis-like response is not as evident in aged animals (21–24 m). These bidirectional effects appear to be mediated via the endocannabinoid CB1 and CB2 receptors.